The camphor tree and the elephant: religion and ecological change in maritime Southeast Asia - Zakaria, Faizah (Culture, place, and nature, 2023)
"Spiritual Anthropocene brings religion into the history of ecological change in Southeast Asia, considering why organized monotheistic religion in the region has largely failed to cultivate the ethics and social will to protect the environment"--